Neurotoxicity studies with a tropomyosin-related kinase A inhibitor, ASP7962, on the sympathetic and sensory nervous systems in rats. (15th June 2021) - Kigami, Daisuke; Butt, Mark T.; Brown, Danielle L.; Matsumoto, Masahiro; Ito, Hiroyuki
Graphical abstract: Highlights: Reversible neuronal atrophy but no neuronal cell death in the sympathetic ganglia. Stereological analysis showed reversible neuronal atrophy in the superior cervical ganglion. TrkA inhibitor did not induce any detectable dysfunction of the sympathetic and sensory nervous system. Abstract: ASP7962 is a small molecule inhibitor for the nerve growth factor (NGF) receptor, tropomyosin-related kinase A (TrkA). NGF contributes to the survival of sensory and sympathetic neurons through TrkA receptor activation. Gross, microscopic, and quantitative effects to the nervous system were evaluated following oral ASP7962 administration to Sprague Dawley rats for 4 weeks and 13 weeks and after a recovery period. Histopathological findings included reversible neuronal atrophy but no neuronal death in the sympathetic ganglia (cervicothoracic ganglion, cranial mesenteric ganglion or superior [cranial] cervical ganglion). Stereological analysis showed reversible decreased ganglion volume and/or decreased neuron size in the superior (cranial) cervical ganglion in both the 4-week and the 13-week repeated dose studies. There were no test article related changes in the brain, dorsal root ganglia with spinal nerve roots or trigeminal ganglia and no functional deficits. ASP7962 did not cause any detectable dysfunction of the sympathetic and sensory nervous system in either study.